The Empowering Teachers with Virtual Art Galleries: Digital Training for Megalithic Heritage Education in Napu Valley Elementary Schools - Kadek Hariana; Yun Ratna Lagandesa; Nashrullah Nashrullah; Muhammad Aqil Muhammad Aqil; Muhammad Fasli (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: The Napu Valley Megalithic Site in Central Sulawesi is a historically significant area of high cultural value that has been nominated as a UNESCO World Heritage Site. However, its educational potential has not been optimally utilized in arts and cultural learning at the elementary school level, largely due to limited digital resources and insufficient teacher proficiency in using technology. Purpose of the Study: This community service program aimed to address these challenges by training 15 teachers at SDN Tamadue to create 3D virtual art galleries using the Artsteps platform. Methods: The program was implemented in three sequential phases: Preparation, Training, and Implementation & Evaluation, following the ADDIE instructional design model. Results: Quantitative results demonstrated significant improvement, with the average teacher competency score rising from 52.4 (pre-test) to 85.6 (post-test), representing a 63.4% increase. Ten virtual galleries were successfully created and deployed in classrooms. Post-training evaluation revealed that 100% of teachers were satisfied, 93.3% rated the content as highly relevant, and 80% committed to continuing their use of Artsteps. Classroom observation confirmed increased student engagement and active participation in local arts and cultural learning